The Presence of a Play Space for Post Disaster Recovery - Sari, Novita; Kurniati, Euis; Evasufi Widi Fajari, Laksmi (Tecno Scientifica Publisher, 2023)
From the year 2000 to the year 2022, Indonesia has had a number of natural disasters that were big enough to be called